Doctor-Patient communication: perception of doctors’ communication skills among patients in selected hospitals in Ibadan Nigeria (2020)
The importance of effective communication between patients and physicians in medical consultations has been previously underscored. This is very critical in the realisation of optimal health outcomes and general wellbeing of patients. While studies have attributed poor patients’ outcomes after consultation to poor services, understaffing, poor remuneration and inefficient structure; evidence from literature suggests poor communication between doctors and patients as an important contributing factor in incidences of conflict between doctors and patients. Thus, this study investigated the perception of doctors’ communication skills among patients in some selected hospitals in Ibadan, Nigeria. Patient Enablement and Satisfaction Model (PESM) served as the theoretical underpinning while survey was adopted as the study design. Multi-stage sampling technique was employed in the selection of human and non-human samples. The city of Ibadan was stratified into local government areas (LGAs) while simple random sampling technique was employed in selecting both the LGAs and the hospitals. A total of 300 copies of the questionnaire were administered, however, 288 copies were found usable. Descriptive statistics expressed in frequency counts and simple percentages were utilized in analysing the data. Findings showed that patients have a positive perception of their doctors' communication skills and the communication patients have during consultation with their doctors enabled them to understand their health conditions and comply with doctors’ recommendations. These findings underscore the importance of patient-centred communication in medical practice and have great implications for achieving desirable health outcomes for patients. The study recommends that doctors in both private and public sector in the country should adopt the patient-doctor approach during consultations.